Corporate governance convergence & implications for Singapore's code. - Ng, Lay Hoon. (2008)
This report re-examines Comparative Corporate Governance in light of recent events and cites a formal adoption of the Anglo-Saxon system as the final step in a country's corporate governance progression cycle. Next it concludes that Singapore should maintain its compy-or-explain approach to corporate governance rather than shift to a mandatory stance a la the Sarbanes-Oxley Act.